Environmental management and social responsibility: A perspective of sustainable actions carried out by a company in the field of agribusiness - Kochhann, Shaiane Caroline; Moiseichyk, Ana Elizabeth; Piveta, Maíra Nunes; Obregon, Sandra Leonara (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2016)
The adoption of environmental practices is the incorporation of a "social role" by companies taking into consideration that they are able to influence and transform a local context through small attitudes embedded in everyday life. Besides generating several improvements, the adoption of social and environmental attitudes by the organizations promote differentiation of other companies, according to the competitive market context, because nowadays, the client looks for more than one product. This study sought, Therefore, check the importance and applicability of environmental management combined with the Social responsibility actions carried out by a small organization in the field of agribusiness. Data collection that allowed the achievement of this study came about through the application of a survey instrument to a sample of 203 people divided between employees, suppliers, customers and society. The results obtained with the application of the research, it was evidenced that the company studied deals with very important social and environmental management issues. The same has already in effect, according to the interviewees, some actions that contemplate the theme and may, however, increase its socially responsible action.